A central role for apathy in the effectiveness of interventions for cancer‐related fatigue. Issue 10 (13th August 2020) - Lacourt, Tamara E.; Heijnen, Cobi J.; Manzullo, Ellen F.; Escalante, Carmen
Abstract: Objective: Cancer‐related fatigue (CRF) affects a substantial number of cancer patients and survivors. Recommendations for CRF treatments are largely based on results of randomized controlled trials. The interpretability of such results is limited to patients eligible and willing to participate in these trials. We aimed to address this limitation in a retrospective study of patients seen at a CRF clinic in a comprehensive cancer center. The objectives were to (a) determine the effectiveness of clinician‐initiated interventions for CRF and identify their mediators and (b) describe the frequency and effectiveness of patient‐initiated physical activity (PA) behavior for alleviating CRF and identify determinants of this PA. Methods: Data (patient‐reported somatic and mood symptoms; clinical data; clinician‐documented changes in medication and behavior) from n = 213 patients collected as part of the clinic's standard of care at initial clinical consult and follow‐up 4 to 11 weeks later were included. Effects of clinician‐initiated interventions and patient‐initiated PA on change in fatigue were analyzed using linear models. Results: Of all clinician‐initiated interventions, only psychostimulant start was recorded frequent enough for further investigation and was associated with reduced fatigue; this association was mediated by a reduction in apathy. PA was also associated with reduced fatigue severity. PA initiation/increase after consult was associated with lower apathy at consult. Conclusions: These results demonstrate a major role for patient apathy in the effectiveness and initiation of CRF‐targeting interventions. Behavioral therapies focusing on reduction in apathy should be considered as initial treatment of CRF in those with substantial apathy.